Diagnostic accuracy of serum prostate specific antigen and prostate imaging reporting and data system score with gold standard histopathology: a prospective study - Raza, Arifa; Khan, Sohail Ahmed; Rafiq, Nida; Raza, Muhammad (International Journal of Pathology, 2025)
Background: Prostate cancer is a considerable health problem. Although serum PSA is a commonly used biomarker, its limitations dictate the need to have more specific diagnostic methods. Multi-parametric MRI, which is interpreted by the use of the PIRADS, has proved to be an attractive modality. Our objective is to compare and contrast the diagnostic validity of PSA and PIRADS scoring for identification of prostate cancer. Methods: A prospective cross-sectional study was carried out on 300 male individuals who were at the risk of having prostate cancer clinically. Each study subject was subjected to PSA testing and multi-parametric MRI. Patients having a high PSA (≥4 ng/mL) and/or a PIRADS score of 3 or higher underwent transrectal ultrasound-directed biopsy using the histopathology as the gold standard. The parameters of diagnostic accuracy (sensitivity, specificity, PPV, NPV, accuracy) were computed. Results: The incidence of prostate cancer was 38.7%. Serum PSA had better diagnostic sensitivity of 91.4, specificity of 82.1 and overall accuracy of 85.7 percent respectively. It had a very high negative predictive value (NPV) of 93.8. Conversely, PIRADS scoring (≥3) depicted a moderate sensitivity of 67.2 and specificity of 82.1 and the accuracy was 76.3. Analysis of stratification showed a high level of performance of PSA in all age groups and ethnicities, whereas PIRADS showed mixed sensitivity, especially lower in some ethnic groups. Conclusion: The results of our study support that due to its exceptional negative predictive value, serum PSA was found to be a sensitive and reliable preliminary test that can exclude the presence of prostate cancer. PIRADS MRI, and scoring system though specific, fail to detect clinically significant cancers. MRI may be used to provide specific biopsy guidance to PSA-positive patients.